Profil pasien baru HIV di poliklinik VCT BRSU Tabanan Bali pada tahun 2009 sampai 2017 - R Prawira Bayu; I Gusti Ngurah Made Budiana Indrawan; Ni Nengah Sukarni; Made Edwin Sridana (Intisari Sains Medis, 2018)
Background: HIV infection is a disease that currently becomes a global problem. Bali is one of the provinces in Indonesia with very high HIV infection new case. Badan Rumah Sakit Umum (BRSU) Tabanan is one of the leading hospitals in Tabanan. Based on data in Voluntary Counseling and Testing (VCT) clinic in BRSU Tabanan, new diagnosed HIV patients are increasing from year to year, so research about new diagnosed HIV patient profile is needed. This research is a descriptive research. Methods: The research design used in this study is cross-sectional study. Population and sample in this study were all newly diagnosed patients with HIV infection in BRSU Tabanan VCT clinic from 2009 to 2017 with a total of 872 people were obtained by total sampling. Secondary data were then processed statistically using statistical software. Results: From this research obtained that new case is the most in the year 2016 (18,5%). With the most patient in age 30 â€“ 39 years old age group (34,9%), male (60.1%), still in employment (22.4%), still living (93.9%), and predicted risk factor heterosexual (93,7%). When the sample is diagnosed HIV most of the patient in stadium 3 (53,6%), with the most clinical sign is weight loss more than 10% in one month (50,2%), and opportunistic infection Candidiasis (55.6%). Conclusions: In an attempt to reduce spreading of HIV, education about transmitted sexual disease and reproduction health are important, especially in high-risk groups.Â